Plasma levels of active Von Willebrand factor are increased in patients with first ST-segment elevation myocardial infarction: A multicenter and multiethnic study. Issue 1 (1st February 2015) - Rutten, B; Maseri, A; Cianflone, D; Laricchia, A; Cristell, N A; Durante, A; Spartera, M; Ancona, F; Limite, L; Hu, D; Li, H; Uren, N G; et al.
Abstract: Aims: Von Willebrand factor (VWF), a key player in hemostasis and thrombosis, is released from endothelial cells during inflammation. Upon release, VWF is processed by ADAMTS13 into an inactive conformation. The aim of our study was to investigate whether plasma levels of active VWF, total VWF, ADAMTS13, osteoprotegerin (OPG) and the ratios between VWF and ADAMTS13 are risk factors for first ST-segment elevation myocardial infarction (STEMI). Methods and results: We assessed 1026 patients with confirmed first STEMI and 652 control subjects from China, Italy and Scotland, within six hours after their cardiovascular event. Median plasma levels of total VWF, active VWF, OPG and ratios VWF/ADAMTS13 were increased, while plasma levels of ADAMTS13 were decreased in patients compared to controls. The odds ratio (OR) of STEMI in patients with high plasma levels of active VWF was 2.3 (interquartile range (IQR): 1.8–2.9), total VWF was 1.8 (1.4–2.3), ADAMTS13 was 0.6 (05–0.8), OPG was 1.6 (1.2–2.0) and high VWF/ADAMTS13 ratios was 1.5 (1.2–2.0). The OR for total VWF, active VWF and ratios VWF/ADAMTS13 remained significant after adjustment for established risk factors, medical treatment, C-reactive protein, total VWF, ADAMTS13 and OPG. When we adjusted for levels of active VWF, the significance of the OR for VWF and ratios VWF/ADAMTS13 disappeared while the OR for active VWF remained significant. Conclusions: We found evidence that plasma levels of active VWF are an independent risk factor for first STEMI in patients from three different ethnic groups. Our findings confirm the presence of VWF abnormalities in patients with STEMI and may be used to develop new therapeutic approaches.